Local Asset Utilization Model for Productive Zakat in Empowering Mustahik LAZNAS Baitulmaal Muamalat East Java - Ahmadun Najah; Abdul Hakim (Management Department Universitas Islam Negeri Sumatera Utara, 2026)
This study analyzes the productive zakat utilization model implemented by LAZNAS Baitulmaal Muamalat East Java through the Oyster Mushroom House program as an effort to increase their economic independence. This study focuses on identifying the productive zakat model implemented in the program and analyzing the managerial aspects in supporting its sustainability. Using a descriptive qualitative approach, data were collected through in-depth interviews and document analysis involving LAZNAS Baitulmaal Muamalat East Java managers and beneficiaries. The results show that the program adopts an integrated productive zakat model consisting of beneficiary selection, entrepreneurship training, provision of production facilities, technical assistance for cultivation, managerial mentoring, and periodic evaluation. Technical assistance improves cultivation skills and production quality, while managerial mentoring strengthens business planning, financial management, and market access. These interventions contribute to increasing the economic capacity and business sustainability of beneficiaries, although income growth remains fluctuating due to production and market constraints. Keywords: LAZNAS, Local Asset Program, Mustahik, Productive Zakat